Improving curriculum delivery: Using a results informed quality improvement model for teen behavioral health education - Gross, Gregory; Ling, Rui; Richardson, Brad (Frontiers in Public Health, 2022)
Adolescence is a critical developmental stage for establishing healthy decision-making processes and behavior patterns. Many interventions such as evidence-based curricula have been implemented to guide adolescents to avoid risk-taking behaviors and improve health and medical knowledge and outcomes. This study presents a participatory approach informed by the Three Stage (3S) Quality Improvement Process model to enhance the quality of curriculum delivery, based on results indicating outcomes achieved, needs for improvement and quality assurance for maintaining the expected outcomes of an evidence-based curriculum. Tests were conducted before and after the intervention. Using threshold levels and measures of change in the tests, instructors participated in guided discussion and analysis of the data to identify where and how instructional improvements should be made and where outcomes were being achieved as expected. This method was used to diagnose variation in results and delivery and identify root causes informing actions to improve curriculum delivery and outcomes. After facilitated discussions, pre and post-tests from subsequent classes were analyzed. The results showed improved test item scores ranging from 2 to 69.5 percent and 7 of 18 items obtained statistical significance following the implementation of the model described. Overall, an increase in the mean percent correct of 17.1 percent was found.